Integration of ethnoecopreneuship, collaborative, and creative economy as an effort for sustainability of mangrove ecotourism - Nyompa, Sukri; Arfan, Amal; Rakib, Muhammad; Sukri, Irwansyah; Juanda, Muhammad Faisal (Journal of Environmental Engineering and Landscape Management, 2025)
In the face of global tourism industry challenges, innovation in tourism services is essential for achieving sustainable development goals. This research aims to address the multifaceted challenges of sustainable mangrove ecotourism in Indonesia through an integrative approach combining ethnoecopreneuship, collaborative, and creative economy. Utilizing participatory rural appraisal (PRA) and focus group discussion (FGD), data analysis combines strengths, weaknesses, opportunities, threats (SWOT) analyses and analytic hierarchy process (AHP) method. The results emphasize the importance of community involvement, ecological considerations, effective promotion, and adoption of digital technology in the sustainability of mangrove ecotourism. The research calls for collaboration among stakeholders, policy emphasis on local government responsibilities, and active involvement of local communities and non-governmental organizations in mangrove conservation and management. This research underscores the potential for sustainable development, aligning with the sustainable development goals (SDGs) and enhancing economic and social outcomes in Indonesia’s mangrove ecotourism sector.